2011
DOI: 10.1210/jc.2010-1167
|View full text |Cite
|
Sign up to set email alerts
|

Do the Effects of Testosterone on Muscle Strength, Physical Function, Body Composition, And Quality of Life Persist Six Months after Treatment in Intermediate-Frail and Frail Elderly Men?

Abstract: The effects of 6-month T treatment on muscle strength, lean mass, and QoL in frail men are not maintained at 6 months post treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
53
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(59 citation statements)
references
References 18 publications
4
53
0
Order By: Relevance
“…Comparatively, lower levels of baseline free testosterone were correlated with an increased risk of incident or worsening mobility limitation in older men of the Framingham Offspring Study (38). In a randomized trial in 274 elderly hypogonadal prefrail or frail males a 6-month testosterone treatment improved muscle mass and strength, but the effects were not maintained at 6 months after treatment (39,40). Presently, testosterone treatment has not yet been shown to reverse frailty in a large randomized trial (41).…”
Section: Discussionmentioning
confidence: 99%
“…Comparatively, lower levels of baseline free testosterone were correlated with an increased risk of incident or worsening mobility limitation in older men of the Framingham Offspring Study (38). In a randomized trial in 274 elderly hypogonadal prefrail or frail males a 6-month testosterone treatment improved muscle mass and strength, but the effects were not maintained at 6 months after treatment (39,40). Presently, testosterone treatment has not yet been shown to reverse frailty in a large randomized trial (41).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, in a recent 12-month trial with 274 intermediate-frail and frail older men, lean body mass and leg muscle strength increased after 6-month treatment with 25-75 mg day 21 testosterone gel, but returned to baseline 6 months after withdrawal from treatment. 13 The differing changes in lean mass and strength between groups appeared to be the direct influence of changing testosterone levels and not secondary treatment-related factors. A similar pattern of on-treatment gains and subsequent losses in muscle mass and strength were reported in a 24-week study of the durability of effects of 12 weeks' administration of oxandrolone on lean body mass, fat mass and several measures of muscle strength.…”
Section: Muscle Function Changes With Adtmentioning
confidence: 91%
“…However, there were no attendant improvements in grip strength or physical function [44]. The follow-up study reported loss of treatment gains during in the 6 months after treatment ceased, concluding that the benefits on the above parameters were entirely hormone-dependent, and that ongoing treatment was likely necessary to reduce frailty [45]. Another trial investigating the effects of resistance training along with testosterone supplementation in frail elderly men found that, although testosterone therapy increased muscle size relative to placebo, muscle strength was not significantly improved, nor was there a significant effect on physical function [46].…”
Section: Testosteronementioning
confidence: 92%